Formation of processes erosion associated with the use and occupation of soil in the Ribeira river basin, city of Santa Rita / PB | Formação de erosão de processos associada ao uso e ocupação do solo na bacia do rio Ribeira, cidade de Santa Rita / PB - Santos, Caio Lima dos; Vital, Saulo Roberto Oliveira (Revista Geama, 2016)
The way the man has appropriated natural resources, has been revealed as the source of many problems in the environment, which has been reflected directly in the depletion of natural resources and quality of life. The erosion and loss of soil are part of these degenerative processes of the natural landscape. The watershed of the river Ribeira, located in Santa Rita, Paraíba State, is a current example of such processes that are directly associated with forms of land use. Actions arising mainly from the extensive cultivation of cane sugar has been revealed through the development of geomorphological processes that mark the landscape through erosional features, such as small fillets, grooves, and gully, plus a large amount of alluvial fans that protrude over the lowlands often silted water bodies.